Immunotherapeutic Potential of Oncolytic Vaccinia Virus - Thorne, Steve H. (Frontiers in Oncology, 2014)
The concept of oncolytic viral therapy was based on the hypothesis that engineering tumor-selectivity into the replication potential of viruses would permit direct destruction of tumor cells as a result of viral-mediated lysis, resulting in amplification of the therapy exclusively within the tumor environment. The immune response raised by the virus was considered to be necessary for the safety of the approach, but also something of a hindrance to optimal therapeutic activity and repeat dosing. However the pre-clinical and subsequent clinical success of several oncolytic viruses expressing selected cytokines has demonstrated the potential for harnessing the immune response as an additional and beneficial mechanism of therapeutic activity within the platform. Over the last few years a variety of novel approaches have been incorporated to try to enhance this immunotherapeutic activity. Several innovative and subtle approaches have moved far beyond the expression of a single cytokine transgene, with the hope of optimizing anti-tumor immunity while having minimal detrimental impact on viral oncolytic activity.